Evaluation of Hypoparathyroidism following Total Thyroidectomy - Haque, Md Nazmul; Khan, Saif Rahman; Akhter, Moshammat Fatima; Bhuiyan, Mohammad Ashequr Rahman; Sarker, Mohammad Zakaria; Sakik, Mahmudul Amin (Bangladesh Journal of Otorhinolaryngology, 2020)
The most common cause of hypoparathyroidism is damage to the glands during thyroid surgery. Parathyroid gland preservation during thyroidectomy is not only desirable, but essential for the effective management of surgical diseases of the thyroid gland Objective: To find out the incidence rate of hypoparathyroidism after total thyroidectomy. Methods: Study Period: 2 years from Jan 2017 to December 2018 Place of Study : National Institute of ENT, Tejgaon, Dhaka Study Design: Prospective Observational Study Sample size: 107 Sampling Technique: Convenient Sampling technique Results: Among the 107 cases 39 cases were malignant comprising 36.45% of the cases. toxic multinodular goitre were 6 cases among 107 cases (5.6%) and rest 62 cases were benign multinodular goitre with or without cystic change and follicular adenomas (57.94 %). 29 cases out of 39 malignant cases were papillary carcinoma of thyroid (74.36% of malignant lesions), 2 cases of medullary Ca thyroid (5.12 % of malignant lesions) rest 8 were follicular carcinoma (20.51% of malignant lesions). 26 out of 107 (24.30%) cases suffered from postoperative hypocalcaemic tetany within 1st-5th POD. Their parathyroid hormones were significantly reduced and serum calcium were also reduced and they required calcium supplementation. In 5 (4.67%) cases there was no sign and symptoms of tetany but their serum parathormone levels were little below normal level but serum calcium levels were normal and therefore no calcium supplementation were given. The rest 76 (71.03%) cases did not show any sign or symptoms of tetany and did not require calcium supplementation. Among the patients who suffered from tetany majority were cases of Carcinoma of thyroid (18 out of 26 patients of hypoparathyroidism) 69.23%, however lateral neck dissection did not seem to affect decline in parathyroid function as 10 out of 18 patients with thyroid malignancy who suffered from postoperative tetany undergone level II to level V neck dissection in addition to total thyroidectomy. Bangladesh J Otorhinolaryngol; October 2020; 26(2): 116-120